2010
DOI: 10.1038/leu.2010.157
|View full text |Cite
|
Sign up to set email alerts
|

HDAC inhibitors augment cytotoxic activity of rituximab by upregulating CD20 expression on lymphoma cells

Abstract: Anti-CD20 antibody rituximab is now essential for the treatment of CD20-positive B-cell lymphomas. Decreased expression of CD20 is one of the major mechanisms underlying both innate and acquired resistance to rituximab. In this study, we show that histone deacetylase (HDAC) inhibitors augment the cytotoxic activity of rituximab by enhancing the surface expression of CD20 antigen on lymphoma cells. HDAC inhibitors, valproic acid (VPA) and romidepsin, increased CD20 expression at protein and mRNA levels in B-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 51 publications
3
80
0
Order By: Relevance
“…9 Here we showed that VPA, at a clinically achievable concentration, 17 interacted with chemotherapeutic agents to induce caspase-independent autophagic cell death through PRKAA activation. This was observed not only in Tand B-lymphoma cell lines, but also in nude-mouse xenograft lymphoma models.…”
Section: Discussionmentioning
confidence: 99%
“…9 Here we showed that VPA, at a clinically achievable concentration, 17 interacted with chemotherapeutic agents to induce caspase-independent autophagic cell death through PRKAA activation. This was observed not only in Tand B-lymphoma cell lines, but also in nude-mouse xenograft lymphoma models.…”
Section: Discussionmentioning
confidence: 99%
“…It has activity in vestibular schwannomas [18,20,21], neoplastic B-cells, ovarian cancer [22,23], prostate adenocarcinoma [24] and T-cell lymphoma [25]. In combination with immunotherapeutics, HDACis and rituximab (ā£-CD20 mAb) have synergistic cytotoxic activity on NHL cells [26][27][28].…”
Section: Introductionmentioning
confidence: 98%
“…Absorbance at 450 nm was analyzed with a microplate reader, and expressed as a percentage of the value of the corresponding untreated cells (23).…”
Section: Methodsmentioning
confidence: 99%